Toward Environmental Citizenship: The Concept of Citizenship and Its Conceptualization in the Context of Global Environmental Challenges - Mravcová, Anna (Studia Philosophiae Christianae, 2023)
The issue of citizenship has been one of the main topics of political thinking since antiquity, when its origins were significantly shaped by classical philosophers, whose ideas are also important for modern thinking. Gradually, with the intensification of globalization many new conceptualizations of the classical concept of citizenship were formulated to address global challenges. These shift away from the basic view of the interconnectedness of citizenship with a specific territory and give humans a wider, global identity with an associated appeal to global responsibility. One such concept is environmental citizenship. This article is aimed at examining the historical development of citizenship, particularly in its republican and liberal versions, and its conceptualisation in the context of environmental problems that overcome national borders. The demands on citizens must be adapted to this reality. This article highlights the growing potential of environmental citizenship as one of the possible key factors for achieving a more sustainable world, which however requires the active involvement of nation-states. ————————— Received: 24/11/2022. Reviewed: 27/03/2023. Accepted: 18/04/2023.